Erythropoietin Over-Expression Protects against Diet-Induced Obesity in Mice through Increased Fat Oxidation in Muscles - Hojman, Pernille (Public Library of Science, 2009)
Erythropoietin can be over-expressed in skeletal muscles by gene electrotransfer, resulting in 100-fold increase in serum EPO and significant increases in haemoglobin levels. Earlier studies have suggested that EPO improves several metabolic parameters when administered to chronically ill kidney patients. Thus we applied the EPO over-expression model to investigate the metabolic effect of EPO in vivo. At 12 weeks, EPO expression resulted in a 23% weight reduction (P<0.01) in EPO transfected obese mice; thus the mice weighed 21.9±0.8 g (control, normal diet,) 21.9±1.4 g (EPO, normal diet), 35.3±3.3 g (control, high-fat diet) and 28.8±2.6 g (EPO, high-fat diet). Correspondingly, DXA scanning revealed that this was due to a 28% reduction in adipose tissue mass. The decrease in adipose tissue mass was accompanied by a complete normalisation of fasting insulin levels and glucose tolerance in the high-fat fed mice. EPO expression also induced a 14% increase in muscle volume and a 25% increase in vascularisation of the EPO transfected muscle. Muscle force and stamina were not affected by EPO expression. PCR array analysis revealed that genes involved in lipid metabolism, thermogenesis and inflammation were increased in muscles in response to EPO expression, while genes involved in glucose metabolism were down-regulated. In addition, muscular fat oxidation was increased 1.8-fold in both the EPO transfected and contralateral muscles. In conclusion, we have shown that EPO when expressed in supra-physiological levels has substantial metabolic effects including protection against diet-induced obesity and normalisation of glucose sensitivity associated with a shift to increased fat metabolism in the muscles.